Valorization of Waste from Lavender Distillation Through Optimized Encapsulation Processes - Nikoletta Solomakou; Dimitrios Fotiou; Efthymia Tsachouridou; Athanasia M. Goula (Foods)
This study evaluated and compared two encapsulation techniques—co-crystallization and ionic gelation—for stabilizing bioactive components derived from lavender distillation residues. Utilizing aqueous ethanol extraction (solid residues) and concentration (liquid residues), phenolic-rich extracts were incorporated into encapsulation matrices and processed under controlled conditions. Comprehensive characterization included encapsulation efficiency (Ef), antioxidant activity (AA), moisture content, hygroscopicity, dissolution time, bulk density, and color parameters (L*, a*, b*). Co-crystallization outperformed ionic gelation across most criteria, achieving significantly higher Ef (>150%) and superior functional properties such as lower moisture content (<0.5%), negative hygroscopicity (−6%), and faster dissolution (<60 s). These features suggested enhanced physicochemical stability and suitability for applications requiring long shelf life and rapid solubility. In contrast, extruded beads exhibited high moisture levels (94.0–95.4%) but allowed better control over morphological features. The work introduced a mild-processing approach applied innovatively to the valorization of lavender distillation waste through structurally stable phenolic delivery systems. By systematically benchmarking two distinct encapsulation strategies under equivalent formulation conditions, this study advanced current understanding in bioactive microencapsulation and offers new tools for developing functional ingredients from aromatic plant by-products.